2009
DOI: 10.2753/jec1086-4415130403
|View full text |Cite
|
Sign up to set email alerts
|

Motivations in Open Source Software Communities: The Mediating Role of Effort Intensity and Goal Commitment

Abstract: As a community-based innovation, the open source software (OSS) development phenomenon has received great attention from researchers and practitioners. Understanding the factors that affect the involvement and contributions of participants in OSS projects is of signifi cance to facilitate project success. This paper investigates the effects of motivation on participant performance in OSS projects, drawing upon self-determination theory to examine how task effort (i.e., effort intensity and goal commitment) med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 82 publications
(128 reference statements)
1
56
1
2
Order By: Relevance
“…Those receiving direct compensation for LOSS contribution accounted for 50.8% of the total. This statistic was significantly higher than those of general OSS motivation studies; David and Shapiro (2008) found that 29% of OSS developers received direct pay, while Ke and Zhang (2009) found the percentage to be only 19.6%. Notwithstanding, 47.6% of developers voluntarily participated in LOSS projects without any direct compensation.…”
Section: Programmer Typescontrasting
confidence: 49%
“…Those receiving direct compensation for LOSS contribution accounted for 50.8% of the total. This statistic was significantly higher than those of general OSS motivation studies; David and Shapiro (2008) found that 29% of OSS developers received direct pay, while Ke and Zhang (2009) found the percentage to be only 19.6%. Notwithstanding, 47.6% of developers voluntarily participated in LOSS projects without any direct compensation.…”
Section: Programmer Typescontrasting
confidence: 49%
“…On the basis of self-determination theory Ryan, 1985, 2002;Ke and Zhang, 2009), we posit that channel-based price differentiation functions as a monetary reward, contingent on customers' channel choice. Such contingent monetary rewards can reduce the person's perceived self-determination by introducing an external locus of causality.…”
Section: Limited Self-determinationmentioning
confidence: 99%
“…Researchers previously reveal that members primarily remain active in a FLOSS project because it gives them a satisfying and enjoying feeling [20,26]. However, as Fang et al show members are not driven by enjoyment from the beginning on.…”
Section: Floss Researchmentioning
confidence: 92%
“…Hence, integrated motivation is supposed to be a relevant driver for developer retention. Finally, existing literature emphasizes feelings of enjoyment and satisfaction for becoming sustained contributors in FLOSS projects [20,26]. Therefore, intrinsic working motives are considered relevant for becoming long-term participants in a FLOSS project.…”
Section: Research Modelmentioning
confidence: 98%